2016
DOI: 10.1177/0899764016643612
|View full text |Cite
|
Sign up to set email alerts
|

Philanthropic Support of National Parks

Abstract: Ostrom's Social-Ecological Systems (SES) framework has infrequently been applied to civil society research. But its focus on collective action may help explain why some national parks are more successful at attracting philanthropic resources to supplement stagnant public funding. We examine two types of charitable supporting organizations: "Friends of" Groups (FOGs), which typically emphasize fundraising, and Cooperating Associations (CAs), which typically emphasize visitor support. Across over 300 national pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Partelow 2015, Partelow and Boda 2015, Guevara et al 2016, Oviedo and Bursztyn 2016, Blythe et al 2017, London et al 2017, Nakandakari et al 2017, Partelow et al 2018a) and forestry (Fleischman et al 2010, Oberlack et al 2015, Davenport et al 2016. However, use of the framework has expanded beyond those resource-use sectors to general food production systems (Marshall 2015), aquaculture systems (Partelow et al 2018b), terrestrial conservation and rangeland management (Falk et al 2012, Risvoll et al 2014, Baur and Binder 2015, Addison and Greiner 2016, Taggart-Hodge and Schoon 2016, Yandle et al 2016, Guariguata et al 2017, watershed management (Madrigal et al 2011, Bal et al 2011, Nagendra and Ostrom 2014, Villamayor-Tomas et al 2014, Bennett and Gosnell 2015, Naiga et al 2015, Silva et al 2015, Falk et al 2016, Hileman et al 2016, marine conservation and marine ecosystem management (Cinner et al 2012, Schlüter et al 2013, Stevenson and Tissot 2014, Ban et al 2015, 2017, Williams and Tai 2016, coastal development (Kanwar et al 2016, Schlüter et al 2019, energy systems …”
Section: Trends and Gaps In The Social-ecological Systems Framework Lmentioning
confidence: 99%
“…Partelow 2015, Partelow and Boda 2015, Guevara et al 2016, Oviedo and Bursztyn 2016, Blythe et al 2017, London et al 2017, Nakandakari et al 2017, Partelow et al 2018a) and forestry (Fleischman et al 2010, Oberlack et al 2015, Davenport et al 2016. However, use of the framework has expanded beyond those resource-use sectors to general food production systems (Marshall 2015), aquaculture systems (Partelow et al 2018b), terrestrial conservation and rangeland management (Falk et al 2012, Risvoll et al 2014, Baur and Binder 2015, Addison and Greiner 2016, Taggart-Hodge and Schoon 2016, Yandle et al 2016, Guariguata et al 2017, watershed management (Madrigal et al 2011, Bal et al 2011, Nagendra and Ostrom 2014, Villamayor-Tomas et al 2014, Bennett and Gosnell 2015, Naiga et al 2015, Silva et al 2015, Falk et al 2016, Hileman et al 2016, marine conservation and marine ecosystem management (Cinner et al 2012, Schlüter et al 2013, Stevenson and Tissot 2014, Ban et al 2015, 2017, Williams and Tai 2016, coastal development (Kanwar et al 2016, Schlüter et al 2019, energy systems …”
Section: Trends and Gaps In The Social-ecological Systems Framework Lmentioning
confidence: 99%
“…This perspective suggests that, as government initiatives increase, NGOs may experience decreased funding or reduced opportunities for independent action. Previous studies have identified this interaction (Yandle et al, 2016).…”
Section: Introductionmentioning
confidence: 76%
“…As highlighted by the interviews, formal agreements offer a clear framework for cooperation, setting out terms, conditions, and expected outcomes. This clarity is especially crucial when dealing with complex societal challenges that require structured interventions (Yandle et al., 2016). Formal agreements ensure accountability, transparency, and mutual understanding, thereby reducing potential disputes over resource allocation.…”
Section: Discussionmentioning
confidence: 99%
“…During the Great Recession, state and local governments faced revenue shortfalls, and public spending for parks and land conservation has yet to rebound to pre‐Recession levels (Barrett, Pitas, and Mowen 2017). Nonprofit organizations emerge to supplement government funding when politicians ignore, or fail to fund, environmental issues (Delfin Jr and Tang 2006; Yandle, Noonan, and Gazley 2016).…”
Section: Overview Of the Literature On Support Nonprofit Philanthropy...mentioning
confidence: 99%